2001
DOI: 10.1002/cc.3
|View full text |Cite
|
Sign up to set email alerts
|

State Policy and Postsecondary Enrollment Options: Creating Seamless Systems

Abstract: Hundreds of thousands of secondary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…As well, recent research (Kurlaender, 2006) has shown that for Latinos, community colleges are the higher education institution of choice. Because of their open access mission and state and local governing bodies that are similar to-and sometimes the same as-those for K-12 schools, community colleges are often better suited to work with both K-12 schools and other community and civic organizations than four-year institutions, facilitating their role in K-12 educational reform initiatives in their communities (Boswell, 2001;Orr and Bragg, 2001). As demand for college increases, community colleges are logical and appropriate institutions to link high school and college for students heretofore underrepresented in higher education.…”
Section: The Role Of the Community College In Academic Pathwaysmentioning
confidence: 97%
“…As well, recent research (Kurlaender, 2006) has shown that for Latinos, community colleges are the higher education institution of choice. Because of their open access mission and state and local governing bodies that are similar to-and sometimes the same as-those for K-12 schools, community colleges are often better suited to work with both K-12 schools and other community and civic organizations than four-year institutions, facilitating their role in K-12 educational reform initiatives in their communities (Boswell, 2001;Orr and Bragg, 2001). As demand for college increases, community colleges are logical and appropriate institutions to link high school and college for students heretofore underrepresented in higher education.…”
Section: The Role Of the Community College In Academic Pathwaysmentioning
confidence: 97%
“…Policy makers and educators have argued that dual enrollment programs and policies offer students many benefits, which include enriching students' senior year of high school (Allen, 2010), diversifying the high school curriculum (Boswell, 2001), preparing students for college and increasing students' college aspirations (Smith, 2007), and reducing time to a college degree and saving students money (Hoffman et al, 2008). Furthermore, there is accumulating evidence that dual enrollment participation positively influences students' college enrollment, college GPA, college persistence, and college completion (Allen & Dadgar, 2012;An, 2013aAn, , 2013bKarp et al, 2007;Taylor, In press).…”
Section: Literature Review Dual Enrollment Programsmentioning
confidence: 99%
“…In addition, articulated courses may reduce duplication, tuition costs, the time required to complete a degree, and wasted time during the senior year. Additionally, articulated courses may increase collaboration among high school and community college faculty and encourage students to attend college (Boswell, 2001).…”
mentioning
confidence: 98%